Strength Characteristics Based on Curing Method and Curing Time of Inorganic Binder Matrix of Ternary System - Lee, Jinwoo; Lee, Sangsoo (Asian Journal of Chemistry, 2015)
This study investigated into cement substitutes using the industrial by-products and applied the blast furnace slag, red mud and silica fume and alkaline activator. In addition, experiments have been carried out by varying the curing method and curing times for preventing crack in matrix using industrial by-products. The results showed that no crack occurred in the matrix cured in water and that such matrix was found to have better strength than the air-dried matrix. Based on that, the experiment was performed to achieve economic efficiency through variation of curing time for water curing temperature. The results suggested that adequate strength was achieved when the water curing time was longer than 6 h at 80 °C.